Драйвер терагерцовых ЛСЭ на базе 20 МэВ-ного линейного ускорителя электронов ЕрФИ - Э. О. Алексанян; Э. М. Лазиев; М. Л. Мовсисян (ՀՀ ԳԱԱ հրատ.)
Рассмотрена возможность использования линейного ускорителя электронов на энергию 20 МэВ ЕрФИ (ЛУЭ-20) в качестве драйвера комплекса лазеров на свободных электронах терагерцового диапазона. An opportunity of using the 20 MeV Linac at YerPhI as a driver of THz-FELs is considered. The basic parameters of the Linac and FELs are given. Requirements to the electron beam and Linac systems are determined.
Keywords: Physics; Science; Radiophysics